Optimal Power Flow Solution for Wind Integrated Power in presence of VSC-HVDC Using Ant Lion Optimization - Ramzi Kouadri; Linda Slimani; Tarek Bouktir; Ismail Musirin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper studies the impact of incorporating wind power generation WPG on the power system on prsence of voltage source converter based high voltage DC (VSC-HVDC). A new meta-heuristic optimization technique are use for solving of the optimal power flow (OPF) problem, this technique optimization namely Ant Lion Optimizer (ALO). The optimization method is the Ant Lion Optimizer (ALO) method for resolve the optimal power flow (OPF) with incorporating of wind power generation on prsence of VSC-HVDC. And we used weibull distribution model of the wind farm. The ALO-OPF method has been examined and tested on standard test systems IEEE 30 bus with objective functions is minimization of cost total of production TPC are contain the sum of thermal and wind generation cost.